Out of the Cave of the Cyclops. Issue 48 (3rd July 2017) - Arthos, John
ABSTRACT: Despite the deep respect that readers continue to discover in the great twentieth-century texts of hermeneutics, the academic career and reputation of Gadamer's philosophical version has fallen into the shadows; it seems a long time since the heady days that it could claim universality as an intellectual koiné. This decline is a genuine shame, because at the peak of its reputation it held out the promise of returning the power of humanistic judgement to greater recognition against the domination of method in an age of technique. Gadamer teased out the unreflective meta-logic of the Western traditions of prudence as an alternative paradigm and powerful antidote to our rationalist excesses. This paper offers one strategy for salvaging that effort and recuperating an important role for philosophical hermeneutics in the academy.